Strategies to improve the fluorescent signal of the tripartite sfGFP system. (24th June 2020) - Shen, Jing; Zhang, Wenlu; Gan, Chunyang; Wei, Xiafei; Li, Jie; Sun, Yuxue; Yuan, Yi; Cai, Xuefei; Long, Quanxin; Cui, Jing; Guo, Haitao; Huang, Ailong; et al.
Abstract: Bimolecular fluorescence complementation (BiFC) is a popular method used to detect protein–protein interactions. For a BiFC assay, a fluorescent protein is usually split into two parts, and the fluorescence is recovered upon the interaction between the fused proteins of interest. As an elegant extension of BiFC, a tripartite superfold green fluorescent protein (sfGFP) system that has the advantages of low background fluorescence and small fusion tag size has been developed. However, the tripartite system exhibits a low fluorescence signal in some cases. To address this problem, we proposed to increase the affinity between the two parts, G1–9 and G11, of the tripartite system by adding affinity pairs. Among the three affinity pairs tested, LgBiT-HiBiT improved both the signal and signal-to-noise (S/N) ratio to the greatest extent. More strikingly, the direct covalent fusion of G11 to G1–9, which converted the tripartite system into a new bipartite system, enhanced the S/N ratio from 20 to 146, which is superior to the bipartite sfGFP system split at 157/158 or 173/174. Our results implied that the 10th β-strand of sfGFP has a low affinity and a good recovery efficiency to construct a robust BiFC system, and this concept might be applied to other fluorescent proteins with similar structure to construct new BiFC systems.